2008
DOI: 10.1016/j.bbabio.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein-2 accumulates rapidly in the inner mitochondrial membrane during mitochondrial reactive oxygen stress in macrophages

Abstract: Uncoupling protein-2 (UCP2) is a member of the inner mitochondrial membrane anion-carrier superfamily. Although mRNA for UCP2 is widely expressed, protein expression is detected in only a few cell types, including macrophages. UCP2 functions by an incompletely defined mechanism, to reduce reactive oxygen species production during mitochondrial electron transport. We observed that the abundance of UCP2 in macrophages increased rapidly in response to treatments (rotenone, antimycin A and diethyldithiocarbamate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 329 publications
(567 reference statements)
2
49
1
1
Order By: Relevance
“…In absence of appropriate mitochondrial uncoupling, a physiological stimulus such as exercise that normally promotes positive brain plasticity can, in fact, result in a deleterious effect, perhaps because of increased production of free radicals. UCP2 has been shown to be a radical scavenger (Echtay et al, 2002;Produit-Zengaffinen et al, 2007;Giardina et al, 2008), which is one of the likely mechanisms via which UCP2 can exert a protective effect on cellular and synaptological adaptations to increased workload on hippocampal neuron triggered by increased voluntary exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In absence of appropriate mitochondrial uncoupling, a physiological stimulus such as exercise that normally promotes positive brain plasticity can, in fact, result in a deleterious effect, perhaps because of increased production of free radicals. UCP2 has been shown to be a radical scavenger (Echtay et al, 2002;Produit-Zengaffinen et al, 2007;Giardina et al, 2008), which is one of the likely mechanisms via which UCP2 can exert a protective effect on cellular and synaptological adaptations to increased workload on hippocampal neuron triggered by increased voluntary exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Although the uncoupling activity of uncoupling proteins may be dependent on acute regulation by endogenous activators such as protonmotive force, fatty acids and reactive alkenals [17,18,20], it is not known whether, or how, such activation is acutely reversed [35]. A plausible mechanism of deactivation of any postulated function of UCP2 is by protein degradation: in ovarian and granulosa cell lines and in macrophages, UCP2 is turned over remarkably rapidly, with a half-life of about 1 h [36,37]. The same is true in INS-1E cells, where the half-life is constant at about 60 min, regardless of the glucose concentration and putative activation state [12].…”
Section: Dynamic Regulation Of Ucp2 Concentration In Pancreatic β-Cellsmentioning
confidence: 99%
“…However, in conjunction with its uncoupling function, UCP2 is also thought to mediate mitochondrial ROS production. Several recent studies have demonstrated that UCP2 acts as a modulator of ROS production in various tissues (Anedda et al 2008, Degasperi et al 2008, Giardina et al 2008. Interestingly, UCP2 has been shown to be activated by ROS molecules themselves (Echtay et al 2002, Krauss et al 2003, potentially representing a feedback loop whereby UCP2 senses mitochondrial ROS and upregulates its expression in an attempt to decrease high ROS production (Giardina et al 2008).…”
Section: Knockout Of Ucp2 Impairs A-cell Function and Contributes To mentioning
confidence: 99%